2021
DOI: 10.1186/s13063-021-05540-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of virtual reality on non-drug behavioral management of short-term dental procedure in children

Abstract: Background Due to the inherent characteristics of immersion, imagination, and interactivity in virtual reality (VR), it might be suitable for non-drug behavior management of children in dental clinics. The purpose of this trial was to measure the role of VR distraction on behavior management in short-term dental procedures in children. Methods A randomized clinical trial design was carried out on 120 children aged between 4 and 8 years to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 38 publications
2
57
0
3
Order By: Relevance
“…SnowWorld was the first immersive VR game designed for pain reduction in patients undergoing burn wound care (Hoffman et al, 2008). In other studies ( n = 20), children experienced a VR adventure during their medical procedure, such as going on a rollercoaster ride, swimming underwater, travelling around the world or enjoying nature (Althumairi et al, 2021; Aydın & Özyazıcıoğlu, 2019; Canares et al, 2021; Chad et al, 2018; Chan et al, 2019; Chau et al, 2018; Chen et al, 2020; Clerc et al, 2021; Erdogan & Aytekin Ozdemir, 2021; Gerçeker et al, 2020; Gerçeker et al, 2021; Goldman & Behboudi, 2021; Knight et al, 2019; Litwin et al, 2021; Ran et al, 2021; Sander Wint et al, 2002; Scapin et al, 2017; Semerci et al, 2021; Ustuner Top and Kuzlu Ayyıldız, 2021; Xiang et al, 2021). Finally, some children selected a cartoon or movie to watch in their VR headset during their dental or needle‐related procedure ( n = 15) (Ali et al, 2021; Alshatrat et al, 2021; Asl Aminabadi et al, 2012; Felemban et al, 2021; Gerçeker et al, 2018; Koticha et al, 2019; Lee et al, 2021; Mbazzi et al, 2021; Mohanasundari et al, 2021; Niharika et al, 2018; Nunna et al, 2019; Rao et al, 2019; Shetty et al, 2019; Toledo Del Castillo et al, 2019; Wong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…SnowWorld was the first immersive VR game designed for pain reduction in patients undergoing burn wound care (Hoffman et al, 2008). In other studies ( n = 20), children experienced a VR adventure during their medical procedure, such as going on a rollercoaster ride, swimming underwater, travelling around the world or enjoying nature (Althumairi et al, 2021; Aydın & Özyazıcıoğlu, 2019; Canares et al, 2021; Chad et al, 2018; Chan et al, 2019; Chau et al, 2018; Chen et al, 2020; Clerc et al, 2021; Erdogan & Aytekin Ozdemir, 2021; Gerçeker et al, 2020; Gerçeker et al, 2021; Goldman & Behboudi, 2021; Knight et al, 2019; Litwin et al, 2021; Ran et al, 2021; Sander Wint et al, 2002; Scapin et al, 2017; Semerci et al, 2021; Ustuner Top and Kuzlu Ayyıldız, 2021; Xiang et al, 2021). Finally, some children selected a cartoon or movie to watch in their VR headset during their dental or needle‐related procedure ( n = 15) (Ali et al, 2021; Alshatrat et al, 2021; Asl Aminabadi et al, 2012; Felemban et al, 2021; Gerçeker et al, 2018; Koticha et al, 2019; Lee et al, 2021; Mbazzi et al, 2021; Mohanasundari et al, 2021; Niharika et al, 2018; Nunna et al, 2019; Rao et al, 2019; Shetty et al, 2019; Toledo Del Castillo et al, 2019; Wong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of all the studies included are reported in Table 2. Out of 10 incoming studies, 3 studies (30%) in Korea [2,24,25] and other studies in Brazil [19], Iran [20], Netherlands [21], Saudi Arabia [22], Republic of Korea [1], Spain [23] and China [3]. Studies in two categories of randomized trial (20%) [21,24] and randomized clinical trial (60%) [1-3, 19, 20, 22, 23, 25] Were classified.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…In 7 of the studies, children and parents were satisfied with the virtual reality intervention in reducing anxiety, and in all 7 cases, users were highly satisfied [1-3, 19, 23-25]. In 3 cases of studies found from virtual reality technology in reducing pediatric anxiety in dentistry [3,19,23], 4 cases before surgery [20,21,24,25], 2 cases related to anxiety before shelf radiography of breasts [1,2] and one case were used during preoperative anesthesia [22].…”
Section: The Effects Of Virtual Reality On Children's Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an experienced dentist was asked to classify children's behavior with FBRS instead of CFSS-DS after treatment. FBRS was widely used to access the behavior of children (34)(35)(36) and the effectiveness of BMTs in children's dental treatment (37,38). The compliance scores were measured by using FBRS after treatment in this study.…”
Section: Frankl Behavior Rating Scalementioning
confidence: 99%